Influence of Self-Relevance and Reputational Concerns on Altruistic Moral Decision Making - Zhan, Youlong; Xiao, Xiao; Tan, Qianbao; Zhang, Shangming; Ou, Yangyi; Zhou, Haibo; Li, Jin; Zhong, Yiping (Frontiers in Psychology, 2019)
Complex moral decision making may share certain cognitive mechanism with economic decision making under risk situations. However, it is little known about how people weigh gains and losses between self and other during moral decision making under risk situations. The current study adopted the dilemma scenario-priming paradigm to examine how self-relevance and reputational concerns influenced moral decision making. Participants were asked to decide whether they were willing to sacrifice own interests to help the protagonist (friend, acquaintance, or stranger) under the dilemmas of reputational loss risk, while the helping choices, decision times and emotional responses were recorded. In Study 1, participants showed a differential altruistic tendency, indicating that participants took shorter times to make more helping choices and subsequently reported weaker unpleasant experience toward friends compared to acquaintances and strangers. In Study 2, participants still made this egoistically biased altruistic choices under the low reputational loss risk conditions. However, such effect was weakened by the high reputational loss risks. Results suggested that moral principle guiding interpersonal moral decision making observed in our study is best described as an egoistically biased altruism, and that reputational concerns can play a key role in restraining selfish tendency.